## anonymous one year ago will fan and medal

1. anonymous

Using the completing-the-square method, rewrite f(x) = x2 − 8x + 3 in vertex form. f(x) = (x − 8)2 f(x) = (x − 4)2 − 13 f(x) = (x − 4)2 + 3 f(x) = (x − 4)2 + 16

2. anonymous

@dan815

3. anonymous

@jim_thompson5910 plz help

4. anonymous

i think B

5. anonymous

how did you get it

6. anonymous

do you think its b ?

7. jim_thompson5910

|dw:1435621592774:dw|

8. jim_thompson5910

|dw:1435621614093:dw|

9. jim_thompson5910

|dw:1435621632111:dw|

10. jim_thompson5910

use the formula h = -b/(2a) to find h. Tell me what you get

11. anonymous

i have no clue how to do this

12. anonymous

i just want someone to help me figure it out

13. jim_thompson5910

do you see how I got b = -8 and a = 1 ??

14. anonymous

yes

15. jim_thompson5910

plug those values into the formula h = -b/(2*a)

16. anonymous

a = 1 b = -1 c = 2 ?????

17. jim_thompson5910

h = -b/(2*a) h = -(-8)/(2*1) h = 4 making sense?

18. anonymous

ooooohhhhhhh, let me explain real quick

19. anonymous

so h = -b/(2*a) is the formula and all i have to do is plug in the numbers ?!?!?!

20. jim_thompson5910

yeah plug in a = 1 and b = -8

21. anonymous

for some reason i read it wrong

22. anonymous

so now what?

23. jim_thompson5910

h = 4, plug this into x of the original equation to find y

24. anonymous

f(x) = x2 − 8x + 3 h = -b/(2*a) x= - 8/6 ????

25. anonymous

am i close

26. jim_thompson5910

replace every x in the original equation with 4 then compute

27. jim_thompson5910

not really

28. anonymous

lol

29. anonymous

f(x) = 8 − 32 + 3

30. jim_thompson5910

|dw:1435622365786:dw|

31. jim_thompson5910

|dw:1435622392834:dw|

32. jim_thompson5910

use PEMDAS or a calculator to compute

33. anonymous

i sorry, i suck at math

34. jim_thompson5910

use a calculator if needed

35. jim_thompson5910

free calculator http://web2.0calc.com/

36. jim_thompson5910

|dw:1435622494155:dw|

37. jim_thompson5910

|dw:1435622519411:dw|

38. anonymous

-13

39. jim_thompson5910

so that is the value of k

40. jim_thompson5910

h = 4 k = -13

41. jim_thompson5910

plug a = 1 h = 4 k = -13 into \[\Large f(x) = a(x-h)^2 + k\]

42. anonymous

f(x)=1(x-4)^2+1-13

43. anonymous

-13*

44. jim_thompson5910

yeah (x-4)^2 - 13

45. anonymous

i don't see that option

46. anonymous

never mind

47. anonymous

thank you for your time and patience

48. anonymous

<3<3<3

49. jim_thompson5910

no problem